Novel role of peptidoglycan recognition protein 2 in activating NOD2-NFκB inflammatory axis in coronary artery disease - Basu, Pratitusti; Das, Apabrita Ayan; Siddiqui, Khawer N.; Mondal, Prakas C.; Bandyopadhyay, Arun (Atherosclerosis, 2024)
The role of inflammation in driving atherosclerosis is well-established. It exerts systemic effects beyond the local site of plaque formation. In the context of coronary artery disease (CAD), the proteins that show altered levels in the plasma, are potentially important for understanding the key regulatory mechanism in the pathogenesis of atherosclerosis. A case-control study revealed that plasma soluble Peptidoglycan Recognition Protein 2 (PGLYRP2) primarily produced by the liver, is increased in subjects with CAD. Furthermore, the concentration of PGLYRP2 in the blood correlates with the severity of coronary artery disease. Thus, it raises interest in understanding the exact role of the protein in aortic inflammation and plaque progression. We evaluated the plasma concentration of PGLYRP2 in three distinct groups: patients with CAD (N = 68), asymptomatic individuals (N = 34), and healthy volunteers (N = 20). Furthermore, we investigated the correlation between disease severity and PGLYRP2 levels in CAD patients. To identify potential binding partners of PGLYRP2, we employed computational analysis. We verified the PGLYRP2-NOD2 interaction in macrophage cells and elucidated the inflammatory pathways activated by PGLYRP2 within these cells. To assess the impact of PGLYRP2, we examined its effects in the atherosclerotic mice model (ApoE−/−). In this study, we report for the first time that Nucleotide-binding Oligomerization domain 2 (NOD2) which is expressed on the surface of macrophages, is a receptor of PGLYRP2. The N-terminal domain of PGLYRP2 directly binds to NOD2 and activates the NOD2-RIP2-NFκB cascade that promotes the secretion of proinflammatory cytokines like TNFα, IL1β, and IL-8. In the atherosclerotic mice model (ApoE−/−) we demonstrate that elevated PGLYRP2 level is parallel with increased proinflammatory cytokines in the plasma when fed a High Cholesterol Diet (HCD). Immunohistochemical analysis reveals that PGLYRP2 is co-localized with NOD2 on the macrophages at the site of the lesion. Taken together, our data demonstrate that NOD2 acts as a receptor of PGLYRP2 on macrophages, which mediates the activation of the NOD2-RIP2-NFκB pathway and promotes inflammation, thus significantly contributing to the development and progression of atherosclerosis. [Display omitted] •Our discovery sheds new light on the mechanism of aortic inflammation and the progression of CAD.•Peptidoglycan Recognition Protein 2 (PGLYRP2) originating from the liver is notably elevated in individuals with CAD.•We uncovered a novel interaction of PGLYRP2 with NOD2 on macrophage cell surface.•This interaction contributes to chronic inflammation, a key aspect of atherosclerosis.•The newfound PGLYRP2-NOD2 link offers fresh insights into chronic, unresolved atheroinflammation.